A nineteenth-century American Reader - Inge, M. Thomas, Editor (Washington, D.C. : United States Information Agency, 1988)
Westward expansion and the American Mission -- The temperament of the Frontiersman -- The influence of the Frontier -- Patterns of Trought -- Tradition and Innovation in Literature -- Social progress -- Divergent civilizations -- Slavery and disunion -- Industrial triumph and Confrontation of Reality
Keywords: American Literature -- 19 th Century; United States -- Civilization - 19Th Century-Sources